2018
DOI: 10.1016/j.jcot.2018.04.016
|View full text |Cite
|
Sign up to set email alerts
|

Rare case of atypical femoral fracture with blocked medullary canal associated with bisphosphonate therapy

Abstract: Bisphosphonates are widely used for treatment of osteoporosis and its use is increasing in geriatric population. Atypical femoral fractures are associated with bisphosphonate therapy. We report an unusual case of femoral shaft fracture following bisphosphonate therapy where the femoral canal of the proximal and distal fracture fragments was blocked and its management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…We found three cases [ 4 - 6 ] of obliterated intramedullary canals during intramedullary nailing for atypical femoral fractures. Such an abnormal morphology is scarcely documented.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We found three cases [ 4 - 6 ] of obliterated intramedullary canals during intramedullary nailing for atypical femoral fractures. Such an abnormal morphology is scarcely documented.…”
Section: Discussionmentioning
confidence: 99%
“…Only 1.1% of femoral fractures are accounted for atypical causes [3]. Although it is rare, the increment of this kind of atypical fracture diagnosis has led to more reporting cases of complications and technical difficulty during the intraoperative period [4][5][6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Still to no avail, they drilled the proximal fragment using a 3.2 mm guide pin. 6 Since no such ideal protocol is still there to deal with blocked medullary canal. Make drill hole with K-wires, then insert guide wire under C-ARM guidance and then ream over it is a guided technique to deal with blocked intramedullary canal.…”
Section: Discussionmentioning
confidence: 99%
“…A minimal number of cases reported atypical fractures of the femur which are related to long-term treatment of bisphosphonates or denosumab [10,11]. ese studies indicated a fracture distinct from the common osteoporosis induced subtrochanteric or femoral sha fracture, while researchers deduced that the possible mechanisms might be microdamage accumulation, increased mineralization, reduced mineralization heterogeneity, variations in bone turnover rates and reduced vascularity and anti-angiogenic e ect related to BPs treatment [12,13].…”
Section: Introductionmentioning
confidence: 99%